The availability of open green space and tree architecture at public senior high schools. (February 2020) - Arlianty, D; Hasanuddin,; Djufri,; Muhibbuddin,; Supriatno,
Abstract: Schools in Banda Aceh city are often traversed by traffic passing vehicles that exhaust emissions such as Pb, CO, NOx, SOx and CO2. The presence of open green space (OGS) is beneficial in cleaning air pollution. Thus, it is necessary to identify the tree architecture model to ensure suitable types of plants in the school's green space area. This study used an exploratory survey method. To measure the OGS ratio, the GPS was used to collect the data to get the proportion of the school area with canopy and then the result was converted to a percentage. The architectural model was identified according to the guidelines from Halle and Oldeman. The results showed that 12 schools in Banda Aceh city meet ideal requirements for the proportion of OGS according to Law No. 26 of 2007, and only one school (SHS 13) does not satisfy the requirements. The highest OGS was identified at SHS 16 (79%); while the lowest is at SHS 13 (28%). The tree architectural models found in this study are Scarrone, Corner, Attims, Troll, Roux, Leeuwenberg, Koriba, Rauh, Aubreville and Stone. The dominating tree architecture model of those schools is the Troll model (35.7%) with 15 species.